Asuhan keperawatan pada Tn. W dengan gangguan sistem hematologi : Anemia defisiensi Fe di ruang gladiol atas RSUD Sukoharjo - AL Khorni, Soif, Fahrun Nur Rosid, S.Kep., Ns., M.Kes (2015)
Background : Fe deficiency anemia is the most anemic in both developed and developing countries. Fe is and elementof the highest in the earth's crust, but Fe deficiency is the most common cause of anemia. This is caused by the human body has a limited ability to absorb Fe and body often experience a loss of Fe caused by excessive bleeding. Goal : To know the description of nursing care in patients with Fe deficiency anemia that include assessment, intervention, implementation and evaluation of nursing. Methods : The method used is to make the process of nursing care I patients with Fe deficiency anemia include assessment, intervention, implementation and evaluation of nursing. Results : The results of nursing assessment is emerging issues such as the easy hair loss, conjungtival pallor, his lips pale, acral felt cold, poor skin turgor, returning more than 3 second, capillary refill back more than 3 second, the value of erythrocytes 2,05 10^6/ul (4,40 - 5,90), hemoglobin 5,2 g/dl (13,2 - 17,3), hematocrit 16,8 % (40 - 52), weight : 50 kg, height 169 cm, IMT : 17,5 (weight less), nutritional status lak of demands, patient food look just exchausted half portion and patients are seen lying in bed. The results of the intervension is the diagnosis of pheriperal tissue perfusion inecffectiveness associated with a decrease in Hb concentration and oxigen suplay given for 6 hours, diagnosis of nutritional imbalance less than body requitments related to the intake of less, anorexia given for 3 hours, and diagnosis of physical mobility impairments related to physical weakness given for 6 hours, partially solved the problems experienced. The result of implementation obstacles is an imbalance in nutrition less than body requitments related to the intake less, anorexia. The results of evaluation is done on the last day of evaluation and intervention to continue until the issue is resolved completely. Conclusion : Cooperation between the health care team and patient or family is indispensable for the success of nursing care in patients so patient nursing problems regarding Peripheral tissue perfusion, nutrition less than body requitments and physical mobility impairments can be performed well and some of the problems can be solved in part.